SISTIM PENGOLAHAN LIMBAH TPA MUARA FAJAR DAN PENGARUH TERHADAP KUALITAS AIR TANAH DI SEKITARNYA - Ertawati Ertawati; Mirna Ilza; Nofrizal Nofrizal (Program Pascasarjana Universitas Riau, 2015)
The result of the research from July to September 2014 at the landfill of RT 01/RW 03 MuaraFajar villages Rumbai sub district in Pekanbaru showed that the waste treatment was lessthan perfect, so that leachate formed as much as 0.4liters/sec at Muara Fajar landfill.Leachate Treatment installation of Muara Fajar landfill is not going well as it should whichcause leachate outlet water not feasible discharge into the environment. Waste treatment andleachate treatment weren’t going well had an effect on the quality of ground water aroundthe landfill, where the unfeasible leachate was discharge to the environment has resultedpermeation in the soil so that the quality of groundwater in monitoring wells 1 wascontaminated. However the overall quality of ground water around the landfill are still belowthe quality standards according to Permenkes No. 416/MENKES/PER/IX/1990 on cleanwater.